Evaluation of spiritual user experience on techno-spiritual application for young children / Fatimah Mamat - Mamat, Fatimah (2014)
Nowadays, as technology entered our lives, it really changed how human thinks and works and touches every aspect of human daily activities including in assisting human's spirituality and religious practices. This emerging technology had called as technospiritual application and has increasing in the website and also in mobile application store. However, there are not many researchers out there doing evaluation on technospiritual to identify the user experience in terms of spirituality after using technospiritual application. Spirituality deals with personal life beliefs and experience towards good deed and later will positively impact to other individuals, societies as well as nature. Thus, the purpose of this study is to evaluate the spiritual user experience by using one example of techno-spiritual application which is Dua 4 Kid. The researcher had evaluated this application for young children which age from five to twelve years old. Dua 4 Kid application is containing of 44 prayers (supplications) acts as tool for young children to learn prayers (supplications). Conducting survey is the main method that researcher had used in this study. The questionnaire was distributed to thirty respondents which randomly choose by researcher. The questionnaire was developed based on Glock and Stack Religious Scale that consist of five dimensions which are thoughts, experience, beliefs, rituals and outcome. This evaluation is also conducted to discover new recommendations of design for improvement to techno-spiritual application. From the result, it was found that young children were very keen to this application and can learnt many kinds of prayers (supplications) from the application at once can increase their spirituality. Towards the end, the result from this study also could be used for future research to enhance the techno-spiritual application.